Clinical Applications of the Eosinophilic Esophagitis Diagnostic Panel - Wen, Ting; Rothenberg, Marc E. (Frontiers in Medicine, 2017)
Abstract: Eosinophilic esophagitis (EoE) is a recently recognized upper gastrointestinal (GI) allergic disorder characterized by esophageal dysfunction (e.g, dysphagia) and esophageal eosinophilia of ≥15 eosinophils/high‐power field (HPF) in patients who have persistent esophagitis on proton pump inhibitor (PPI) therapy. The histologic method is the gold standard of EoE diagnosis. However, EoE clinical symptoms do not always correlate with histology, and the histologic method has sensitivity and specificity issues due to the patchiness of EoE and the subjective nature of the method. The “EoE transcriptome” was initially discovered in 2006, which led to the invention of the EoE diagnostic panel (EDP). In addition to providing a definitive EoE diagnosis with high accuracy, the EDP has been useful in elucidating several key elements about the disease such as the efficacy of specific drugs such as swallowed glucocorticoids and anti–IL-13 humanized antibody therapy, the relationship between EoE and proton pump inhibitor–responsive esophageal eosinophilia (PPI-REE), and predicting the disease course and responsiveness to therapy. The EDP’s long-term potential lies in its plasticity to incorporate new genes and uncover novel disease pathogenesis. We expect that the EDP will be increasingly helpful for personalized medicine approaches and improved diagnostics and disease monitoring.